Photoluminescence and electroluminescence imaging of perovskite solar cells. (December 2015) - Hameiri, Ziv; Mahboubi Soufiani, Arman; Juhl, Mattias K.; Jiang, Liangcong; Huang, Fuzhi; Cheng, Yi‐Bing; Kampwerth, Henner; Weber, Juergen W.; Green, Martin A.; Trupke, Thorsten
Abstract: Fast camera‐based luminescence‐imaging measurements on perovskite solar cells are presented. The fundamental correlation between the luminescence intensity and the open circuit voltage predicted by the generalised Planck law is confirmed, enabling various quantitative methods for the detection of efficiency‐limiting defects to be applied to this new cell structure. Interstinegly, it is found that this fundamental correlation is valid only for light‐soaked devices. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Fast (0.8 s) camera‐based (a) photoluminescence and (b) electroluminescence‐imaging measurements on perovskite solar cells.